Hubungan Status Karies Gigi dengan Status Gizi pada Anak Tk Satu Atap di Kabupaten Aceh Besar - Muna Navisah; Cut Aja Nuraskin (Lembaga Pengembangan Kinerja Dosen, 2024)
Dental caries that often occur in children are often not treated or treated which results in a disturbance in the process of mastication function. The impact of mastication disorder will affect the decrease in the frequency of eating due to discomfort and pain when chewing. This causes growth and development disorders that can affect nutritional status in children. Research was conducted to find out the relationship between dental caries status and nutritional status in One Roof Kindergarten children in Aceh Besar Regency. This research is an analytical research using cross sectional design. The population taken in this study is all children aged 5 - 6 years at TK Satu Atap Aceh Besar Regency. Data collection is done by measuring height, weight and looking for nutritional status indexes using the dietducate application. As well as measuring dental caries with the def-t measurement method. The number of respondents in this study was 41 children. There is a relationship between the status of dental caries and the nutritional status of TK Satu Atap in Aceh Besar with the value (P=0.025) ἀ ≤ 0, 05. The conclusion of this study shows that there is a relationship between dental caries status and nutritional status in children in kindergarten Satu Atap Aceh Besar Regency.